Double-network reinforced cement-based composite material and preparation method thereof

By doping yarns and fibers in the cement matrix, a dispersed network structure is constructed and overlapping with the fiber fabric mesh, the problem of inconsistent mechanical strength of existing fiber fabric-reinforced cement matrix composite materials in different directions is solved, and the consistency of the mechanical strength of concrete in different directions and the improvement of structural reinforcement effect is achieved.

CN119683925AInactive Publication Date: 2025-03-25SHANGQIU NORMAL UNIVERSITY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311231764.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-22
Publication Date
2025-03-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The inconsistent mechanical strength of existing fiber fabric-reinforced cement matrix composites in different directions limits the application of concrete and may lead to safety hazards in structural reinforcement design.

Method used

By doping yarns and fibers into the cement matrix, a dispersed network structure is constructed, overlapping with the fiber fabric mesh, improving the mechanical strength of concrete in different directions.

Benefits of technology

The consistency of the mechanical strength of concrete in different directions is achieved, the structural reinforcement effect and material utilization rate are improved, and the safety hazards in structural reinforcement design are reduced.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a dual-network reinforced cement-based composite material and a preparation method thereof, and belongs to the technical field of building concrete. The composite material comprises a cement matrix and a fiber fabric embedded in the cement matrix, the fiber fabric is laid in the cement matrix, and fibers and yarns are doped in the cement matrix. The preparation method comprises the following steps: mixing and stirring the cement, the fly ash, the silica fume, the mineral powder, the fine river sand and the water, then adding the fibers and the yarns, and continuously stirring and mixing uniformly to prepare matrix slurry; pouring the base body slurry to form a layer of base body, laying a fiber fabric on the base body and embedding the fiber fabric into the surface of the base body; and pouring the matrix slurry on the matrix again, and after pouring is completed, smoothing and troweling the surface and carrying out maintenance, so that the dual-network reinforced cement-based composite material is prepared. According to the invention, a dispersed network structure is constructed by doping yarns and fibers in a cement matrix, and is overlapped with a fiber fabric grid, so that the mechanical strength of the concrete in different directions is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building concrete, and in particular relates to a double-network reinforced cement-based composite material and a preparation method thereof. Background Art

[0002] Fiber fabric reinforced cement-based composites have been widely used in the reinforcement of masonry and concrete structures due to their high tensile strength, high tensile strain and multi-crack characteristics. The tensile strength of fiber fabric reinforced cement-based composites and the utilization rate of embedded fiber fabrics significantly affect the reinforcement effect of the structure and the utilization rate of materials. If the strength of the fiber fabric is not fully utilized, not only will the reinforcement materials such as fiber fabric and cement-based matrix be wasted, but the tensile strength of the fiber fabric reinforced cement-based composite will also be overestimated. This will lead to serious structural safety hazards in structural reinforcement design, and even cause partial or overall collapse of the structure under extreme conditions such as earthquakes, endangering the life and property safety of the users of the reinforced structure.

[0003] At present, the main methods to improve the tensile strength of fiber fabric reinforced cement-based composite materials include increasing the coating permeability of fiber fabric, using higher strength fiber fabric, sticking sand on the fiber fabric surface, applying prestress to the fiber fabric, adding barbs to the ends of the fiber fabric, etc. For example, patent publication number CN101666137A uses basalt fiber and carbon fiber to weave a mixed fabric grid in an interlaced manner, and uses the advantages of carbon fiber's high strength and high elasticity to improve the strength of concrete. However, the fiber fabric is usually laid horizontally in the cement matrix, resulting in inconsistent strength of the concrete in different directions, which limits the application of concrete. Summary of the invention

[0004] In response to the above technical problems, the present invention proposes a double-network reinforced cement-based composite material and a preparation method thereof. By doping yarn and fiber into the cement matrix, a dispersed network structure is constructed, which overlaps with the fiber fabric grid to improve the mechanical strength of concrete in different directions.

[0005] In order to achieve the above object, the technical solution of the present invention is achieved as follows:

[0006] A double-network reinforced cement-based composite material comprises a cement matrix and a fiber fabric embedded in the cement matrix, wherein the fiber fabric is laid in the cement matrix, and the cement matrix is ​​doped with fibers and yarns.

[0007] The fiber fabric is woven from radial fiber bundles and weft fiber bundles. The mesh spacing formed by the weft fiber bundles and the radial fiber bundles in the fiber fabric is 5-35 mm, and the shape of the mesh is one of a rectangle, a rhombus, and a triangle.

[0008] The surface of the fiber fabric is coated with an epoxy resin coating, and the average thickness of the epoxy resin coating is 0.1-0.3 mm.

[0009] The cement matrix is ​​made of the following materials in corresponding parts by mass: 300-500 parts of cement, 200-500 parts of fly ash, 60-70 parts of silica fume, 88-176 parts of mineral powder, 400-425 parts of fine river sand and 300-400 parts of water.

[0010] The fiber is polyvinyl alcohol fiber, the length of the fiber is 10-30 mm, and the aspect ratio of the fiber is 300-600.

[0011] The fiber is mixed in an amount of 0.5-2.0% of the volume of the cement matrix.

[0012] The yarn is cotton yarn, polyester yarn, nylon yarn or wool yarn.

[0013] The length of the yarn is 10-50 mm.

[0014] The yarn is doped in an amount of 0.5-1.0% of the volume of the cement matrix.

[0015] A method for preparing a double-network reinforced cement-based composite material comprises the following steps:

[0016] (1) Cement, fly ash, silica fume, mineral powder, fine river sand and water are mixed and stirred, and then fibers and yarns are added and stirred and mixed to obtain a matrix slurry;

[0017] (2) pouring the matrix slurry to form a matrix layer, laying the fiber fabric on the matrix and embedding it into the matrix surface;

[0018] (3) Repeat step (2) until the number of fiber fabric layers reaches the target requirement, and pour the matrix slurry on the substrate again. After pouring, smooth the surface and perform curing to obtain a double-network reinforced cement-based composite material.

[0019] Beneficial effects of the present invention: The present invention constructs a dispersed network structure by doping yarns and fibers into a cement matrix, which overlaps with the fiber fabric grid and improves the mechanical strength of concrete in different directions. DETAILED DESCRIPTION

[0020] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0021] Example 1

[0022] A double network reinforced cement-based composite material with a thickness of 15 mm, including a cement matrix and a fiber fabric laid in the cement matrix. The fiber fabric is arranged horizontally, and the thickness of the upper and lower cement matrices is 8 mm. The fiber fabric is woven with warp fiber bundles and weft fiber bundles, and the warp fiber bundles and weft fiber bundles are made of carbon fibers. The surface density of the fiber fabric is 80 g / m 2 The mesh spacing of the fiber fabric is 20 mm. The surface of the fiber fabric is coated with a layer of epoxy resin coating with a thickness of 0.1 mm to fix the mesh shape of the fiber fabric.

[0023] The cement matrix is ​​made of the following mass ratio components, cement: fly ash: silica ash: mineral powder: fine river sand: fiber: yarn: water = 447: 495: 60: 176: 425: 5: 5: 354, wherein the fiber is PVA short fiber, wherein the PVA fiber has an aspect ratio of 308, a length of 12 mm, a diameter of 39 μm, a tensile strength of 1600 MPa, an elastic modulus of 40 GPa, an elongation of 7%, and a density of 1.29 g / cm 3 The yarn is polyester yarn with a length of 20 mm. The cement is PO42.5 silicate cement; the fly ash is Class I fly ash; the silica ash has a ignition loss of 3%, a silicon dioxide content of 87%, and a specific surface area of ​​15700 m 2 / kg; the mineral powder is S95 grade, and the content of active calcium, silicon and aluminum inorganic matter is 31%; the particle size of fine river sand is not more than 1.05mm. The preparation method of the above-mentioned double network reinforced cement-based composite material includes the following steps:

[0024] (1) Cement, fly ash, silica fume, mineral powder, fine river sand and water are mixed and stirred, and then fibers and yarns are added and stirred and mixed to obtain a matrix slurry;

[0025] (2) pouring the matrix slurry to form a matrix layer, laying the fiber fabric on the matrix and embedding it into the matrix surface;

[0026] (3) pouring the matrix slurry on the substrate again, smoothing the surface and performing curing after the pouring is completed, thereby obtaining a double-network reinforced cement-based composite material.

[0027] Example 2

[0028] A double network reinforced cement-based composite material with a thickness of 15 mm, including a cement matrix and a fiber fabric laid in the cement matrix. The fiber fabric is arranged horizontally, and the thickness of the upper and lower cement matrices is 8 mm. The fiber fabric is woven with warp fiber bundles and weft fiber bundles, and the warp fiber bundles and weft fiber bundles are made of carbon fibers. The surface density of the fiber fabric is 80 g / m 2The mesh spacing of the fiber fabric is 20 mm. The surface of the fiber fabric is coated with a layer of epoxy resin coating with a thickness of 0.1 mm to fix the mesh shape of the fiber fabric.

[0029] The cement matrix is ​​made of the following mass ratio components: cement: fly ash: silica fume: mineral powder: fine river sand: fiber: yarn: water = 300: 435: 64: 176: 425: 5: 5: 354, wherein the fiber is PVA short fiber, wherein the PVA fiber has an aspect ratio of 350, a length of 10 mm, a diameter of 39 μm, a tensile strength of 1600 MPa, an elastic modulus of 40 GPa, an elongation of 7%, and a density of 1.29 g / cm 3 The yarn is polyester yarn with a length of 10 mm. The cement is PO42.5 silicate cement; the fly ash is Class I fly ash; the silica ash has a ignition loss of 3%, a silicon dioxide content of 87%, and a specific surface area of ​​15700 m 2 / kg; the mineral powder is S95 grade, and its active calcium, silicon and aluminum inorganic matter content is 31%; the particle size of fine river sand is not more than 1.05mm.

[0030] The preparation method of the above-mentioned double network reinforced cement-based composite material comprises the following steps:

[0031] (1) Cement, fly ash, silica fume, mineral powder, fine river sand and water are mixed and stirred, and then fibers and yarns are added and stirred and mixed to obtain a matrix slurry;

[0032] (2) pouring the matrix slurry to form a matrix layer, laying the fiber fabric on the matrix and embedding it into the matrix surface;

[0033] (3) pouring the matrix slurry on the substrate again, smoothing the surface and performing curing after the pouring is completed, thereby obtaining a double-network reinforced cement-based composite material.

[0034] Example 3

[0035] A double network reinforced cement-based composite material with a thickness of 15 mm, including a cement matrix and a fiber fabric laid in the cement matrix. The fiber fabric is arranged horizontally, and the thickness of the upper and lower cement matrices is 8 mm. The fiber fabric is woven with warp fiber bundles and weft fiber bundles, and the warp fiber bundles and weft fiber bundles are made of carbon fibers. The surface density of the fiber fabric is 80 g / m 2 The mesh spacing of the fiber fabric is 20 mm. The surface of the fiber fabric is coated with a layer of epoxy resin coating with a thickness of 0.1 mm to fix the mesh shape of the fiber fabric.

[0036] The cement matrix is ​​made of the following mass ratio components: cement: fly ash: silica fume: mineral powder: fine river sand: fiber: yarn: water = 447: 495: 60: 176: 425: 5: 5: 354, wherein the fiber is PVA short fiber, wherein the PVA fiber has an aspect ratio of 308, a length of 12 mm, a diameter of 39 μm, a tensile strength of 1600 MPa, an elastic modulus of 40 GPa, an elongation of 7%, and a density of 1.29 g / cm 3 The yarn is polyester yarn with a length of 30 mm. The cement is PO42.5 silicate cement; the fly ash is Class I fly ash; the silica ash has a ignition loss of 3%, a silicon dioxide content of 87%, and a specific surface area of ​​15700 m 2 / kg; the mineral powder is S95 grade, and its active calcium, silicon and aluminum inorganic matter content is 31%; the particle size of fine river sand is not more than 1.05mm.

[0037] The preparation method of the above-mentioned double network reinforced cement-based composite material comprises the following steps:

[0038] (1) Cement, fly ash, silica fume, mineral powder, fine river sand and water are mixed and stirred, and then fibers and yarns are added and stirred and mixed to obtain a matrix slurry;

[0039] (2) pouring the matrix slurry to form a matrix layer, laying the fiber fabric on the matrix and embedding it into the matrix surface;

[0040] (3) pouring the matrix slurry on the substrate again, smoothing the surface and performing curing after the pouring is completed, thereby obtaining a double-network reinforced cement-based composite material.

[0041] Example 4

[0042] A double network reinforced cement-based composite material, the thickness of the composite material is 30mm, including a cement matrix and a fiber fabric laid in the cement matrix, two layers of fiber fabric are arranged horizontally, and the cement matrix is ​​divided into three parts: upper, middle and lower, and the thickness of the cement matrix in the upper, middle and lower parts is 10mm. The fiber fabric is woven by warp fiber bundles and weft fiber bundles, and the warp fiber bundles and weft fiber bundles are made of carbon fiber, and the surface density of the fiber fabric is 80g / m 2 The mesh spacing of the fiber fabric is 20 mm. The surface of the fiber fabric is coated with a layer of epoxy resin coating with a thickness of 0.1 mm to fix the mesh shape of the fiber fabric.

[0043] The cement matrix is ​​made of the following mass ratio components: cement: fly ash: silica fume: mineral powder: fine river sand: fiber: yarn: water = 447: 495: 60: 176: 425: 5: 5: 354, wherein the fiber is PVA short fiber, wherein the PVA fiber has an aspect ratio of 308, a length of 12 mm, a diameter of 39 μm, a tensile strength of 1600 MPa, an elastic modulus of 40 GPa, an elongation of 7%, and a density of 1.29 g / cm 3 The yarn is polyester yarn with a length of 50 mm. The cement is PO42.5 silicate cement; the fly ash is Class I fly ash; the silica ash has a ignition loss of 3%, a silicon dioxide content of 87%, and a specific surface area of ​​15700 m 2 / kg; the mineral powder is S95 grade, and its active calcium, silicon and aluminum inorganic matter content is 31%; the particle size of fine river sand is not more than 1.05mm.

[0044] The preparation method of the above-mentioned double network reinforced cement-based composite material comprises the following steps:

[0045] (1) Cement, fly ash, silica fume, mineral powder, fine river sand and water are mixed and stirred, and then fibers and yarns are added and stirred and mixed to obtain a matrix slurry;

[0046] (2) pouring the matrix slurry to form a matrix layer, laying the fiber fabric on the matrix and embedding it into the matrix surface;

[0047] (3) pouring the matrix slurry on the substrate again, laying the fiber fabric on the substrate and embedding it into the surface of the substrate, pouring the matrix slurry on the substrate again, smoothing the surface after pouring and performing curing, and obtaining a double network reinforced cement-based composite material.

[0048] Example 5

[0049] A double network reinforced cement-based composite material, the thickness of the composite material is 30mm, including a cement matrix and a fiber fabric laid in the cement matrix, two layers of fiber fabric are arranged horizontally, and the cement matrix is ​​divided into three parts: upper, middle and lower, and the thickness of the cement matrix in the upper, middle and lower parts is 10mm. The fiber fabric is woven by warp fiber bundles and weft fiber bundles, and the warp fiber bundles and weft fiber bundles are made of carbon fiber, and the surface density of the fiber fabric is 80g / m 2 The mesh spacing of the fiber fabric is 20 mm. The surface of the fiber fabric is coated with a layer of epoxy resin coating with a thickness of 0.1 mm to fix the mesh shape of the fiber fabric.

[0050] The cement matrix is ​​made of the following mass ratio components: cement: fly ash: silica fume: mineral powder: fine river sand: fiber: yarn: water = 447: 495: 60: 176: 425: 5: 5: 354, wherein the fiber is PVA short fiber, wherein the PVA fiber has an aspect ratio of 308, a length of 12 mm, a diameter of 39 μm, a tensile strength of 1600 MPa, an elastic modulus of 40 GPa, an elongation of 7%, and a density of 1.29 g / cm 3 The yarn is cotton yarn with a length of 20 mm. The cement is PO42.5 silicate cement; the fly ash is Class I fly ash; the silica ash has a loss on ignition of 3%, a silicon dioxide content of 87%, and a specific surface area of ​​15700 m 2 / kg; the mineral powder is S95 grade, and its active calcium, silicon and aluminum inorganic matter content is 31%; the particle size of fine river sand is not more than 1.05mm.

[0051] The preparation method of the above-mentioned double network reinforced cement-based composite material comprises the following steps:

[0052] (1) Cement, fly ash, silica fume, mineral powder, fine river sand and water are mixed and stirred, and then fibers and yarns are added and stirred and mixed to obtain a matrix slurry;

[0053] (2) pouring the matrix slurry to form a matrix layer, laying the fiber fabric on the matrix and embedding it into the matrix surface;

[0054] (3) pouring the matrix slurry on the substrate again, laying the fiber fabric on the substrate and embedding it into the surface of the substrate, pouring the matrix slurry on the substrate again, smoothing the surface after pouring and performing curing, and obtaining a double network reinforced cement-based composite material.

[0055] Example 6

[0056] A double network reinforced cement-based composite material, the thickness of the composite material is 30mm, including a cement matrix and a fiber fabric laid in the cement matrix, two layers of fiber fabric are arranged horizontally, and the cement matrix is ​​divided into three parts: upper, middle and lower, and the thickness of the cement matrix in the upper, middle and lower parts is 10mm. The fiber fabric is woven by warp fiber bundles and weft fiber bundles, and the warp fiber bundles and weft fiber bundles are made of carbon fiber, and the surface density of the fiber fabric is 80g / m 2 The mesh spacing of the fiber fabric is 20 mm. The surface of the fiber fabric is coated with a layer of epoxy resin coating with a thickness of 0.1 mm to fix the mesh shape of the fiber fabric.

[0057] The cement matrix is ​​made of the following mass ratio components: cement: fly ash: silica fume: mineral powder: fine river sand: fiber: yarn: water = 447: 495: 60: 176: 425: 5: 5: 354, wherein the fiber is PVA short fiber, wherein the PVA fiber has an aspect ratio of 308, a length of 12 mm, a diameter of 39 μm, a tensile strength of 1600 MPa, an elastic modulus of 40 GPa, an elongation of 7%, and a density of 1.29 g / cm 3 The yarn is nylon yarn with a length of 40 mm. The cement is PO42.5 silicate cement; the fly ash is Class I fly ash; the silica ash has a ignition loss of 3%, a silicon dioxide content of 87%, and a specific surface area of ​​15700 m 2 / kg; the mineral powder is S95 grade, and its active calcium, silicon and aluminum inorganic matter content is 31%; the particle size of fine river sand is not more than 1.05mm.

[0058] The preparation method of the above-mentioned double network reinforced cement-based composite material comprises the following steps:

[0059] (1) Cement, fly ash, silica fume, mineral powder, fine river sand and water are mixed and stirred, and then fibers and yarns are added and stirred and mixed to obtain a matrix slurry;

[0060] (2) pouring the matrix slurry to form a matrix layer, laying the fiber fabric on the matrix and embedding it into the matrix surface;

[0061] (3) pouring the matrix slurry on the substrate again, laying the fiber fabric on the substrate and embedding it into the surface of the substrate, pouring the matrix slurry on the substrate again, smoothing the surface after pouring and performing curing, and obtaining a double network reinforced cement-based composite material.

[0062] Example 7

[0063] A double network reinforced cement-based composite material, the thickness of the composite material is 30mm, including a cement matrix and a fiber fabric laid in the cement matrix, two layers of fiber fabric are arranged horizontally, and the cement matrix is ​​divided into three parts: upper, middle and lower, and the thickness of the cement matrix in the upper, middle and lower parts is 10mm. The fiber fabric is woven by warp fiber bundles and weft fiber bundles, and the warp fiber bundles and weft fiber bundles are made of carbon fiber, and the surface density of the fiber fabric is 80g / m 2 The mesh spacing of the fiber fabric is 20 mm. The surface of the fiber fabric is coated with a layer of epoxy resin coating with a thickness of 0.1 mm to fix the mesh shape of the fiber fabric.

[0064] The cement matrix is ​​made of the following mass ratio components: cement: fly ash: silica fume: mineral powder: fine river sand: fiber: yarn: water = 500: 500: 60: 150: 400: 20: 10: 400, wherein the fiber is PVA short fiber, wherein the PVA fiber has an aspect ratio of 308, a length of 12 mm, a diameter of 39 μm, a tensile strength of 1600 MPa, an elastic modulus of 40 GPa, an elongation of 7%, and a density of 1.29 g / cm 3 The yarn is polyester yarn with a length of 20 mm. The cement is PO42.5 silicate cement; the fly ash is Class I fly ash; the silica ash has a ignition loss of 3%, a silicon dioxide content of 87%, and a specific surface area of ​​15700 m 2 / kg; the mineral powder is S95 grade, and its active calcium, silicon and aluminum inorganic matter content is 31%; the particle size of fine river sand is not more than 1.05mm.

[0065] The preparation method of the above-mentioned double network reinforced cement-based composite material comprises the following steps:

[0066] (1) Cement, fly ash, silica fume, mineral powder, fine river sand and water are mixed and stirred, and then fibers and yarns are added and stirred and mixed to obtain a matrix slurry;

[0067] (2) pouring the matrix slurry to form a matrix layer, laying the fiber fabric on the matrix and embedding it into the matrix surface;

[0068] (3) pouring the matrix slurry on the substrate again, laying the fiber fabric on the substrate and embedding it into the surface of the substrate, pouring the matrix slurry on the substrate again, smoothing the surface after pouring and performing curing, and obtaining a double network reinforced cement-based composite material.

[0069] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A double network reinforced cement-based composite material, comprising a cement matrix and a fiber fabric embedded in the cement matrix, characterized in that: The fiber fabric is laid in a cement matrix in which fibers and yarns are mixed.

2. The double network reinforced cement-based composite material according to claim 1, characterized in that: The fiber fabric is woven from radial fiber bundles and weft fiber bundles. The mesh spacing formed by the weft fiber bundles and the radial fiber bundles in the fiber fabric is 5-35 mm, and the shape of the mesh is one of a rectangle, a rhombus, and a triangle.

3. The double network reinforced cement-based composite material according to claim 2, characterized in that: The surface of the fiber fabric is coated with an epoxy resin coating, and the average thickness of the epoxy resin coating is 0.1-0.3 mm.

4. The double network reinforced cement-based composite material according to claim 3, characterized in that: The cement matrix is ​​made of the following materials in corresponding parts by mass: 300-500 parts of cement, 200-500 parts of fly ash, 60-70 parts of silica fume, 88-176 parts of mineral powder, 400-425 parts of fine river sand and 300-400 parts of water.

5. The double network reinforced cement-based composite material according to any one of claims 1 to 4, characterized in that: The fiber is polyvinyl alcohol fiber, the length of the fiber is 10-30 mm, and the aspect ratio of the fiber is 300-600.

6. The double network reinforced cement-based composite material according to claim 5, characterized in that: The fiber is mixed in an amount of 0.5-2.0% of the volume of the cement matrix.

7. The double network reinforced cement-based composite material according to claim 6, characterized in that: The yarn is cotton yarn, polyester yarn, nylon yarn or wool yarn.

8. The double network reinforced cement-based composite material according to claim 1, characterized in that: The length of the yarn is 10-50 mm.

9. The double network reinforced cement-based composite material according to claim 1, characterized in that: The yarn is doped in an amount of 0.5-1.0% of the volume of the cement matrix.

10. The method for preparing the double network reinforced cement-based composite material according to any one of claims 1 to 9, characterized in that: The following steps are involved: (1) Cement, fly ash, silica fume, mineral powder, fine river sand and water are mixed and stirred, and then fibers and yarns are added and stirred and mixed to obtain a matrix slurry; (2) pouring the matrix slurry to form a matrix layer, laying the fiber fabric on the matrix and embedding it into the matrix surface; (3) Repeat step (2) until the number of fiber fabric layers reaches the target requirement, and pour the matrix slurry on the substrate again. After pouring, smooth the surface and perform curing to obtain a double-network reinforced cement-based composite material.

Citation Information

Patent Citations

  • Hybrid fabric grid made from carbon fiber and basalt fiber

    CN101666137A